Vitamin D supplementation positively affects anthropometric indices: Evidence obtained from an umbrella meta-analysis - Musazadeh, Vali; Zarezadeh, Meysam; Ghalichi, Faezeh; Kalajahi, Fateme Hamedi; Ghoreishi, Zohreh (Frontiers in Nutrition, 2022)
Despite the growing evidence from meta-analyses on vitamin D's anti-obesity properties, their results are controversial. The current umbrella review was performed to assess the available evidence and provide a conclusive explanation in this regard. The international databases PubMed, Scopus, Embase, Web of Science and Google Scholar were systematically searched till March, 2022. A random-effects model was used to run the meta-analysis. All meta-analyses that examined the effect of vitamin D supplementation on BW, BMI, WC, and fat mass were included. Findings of 14 meta-analyses revealed that vitamin D supplementation reduced body mass index (BMI) (ES: -0.11 kg/m2; 95% CI: -0.18, -0.05, p˂0.001; I2=61.0 %, p<0.001), and waist circumference (WC) (ES= -0.79 cm; 95% CI: -1.20, -0.37; p< 0.001; I2= 46.5%, p= 0.096) in comparison to control group. However, the effects of vitamin D on body weight (ES= -0.16 kg, 95% CI: -0.36, 0.04; p= 0.125; I2= 57.0%, p= 0.017), and fat mass (ES: 0.02, 95% CI: -0.20, 0.24, p=0.868; I2= 0.0%, p= 0.531) were not considerable. Vitamin D supplementation significantly improved levels of obesity indices such as BMI, and WC.